Exploring and evaluating the in vitro antifungal, antibiofilm and antitoxin efficacy of Artabotrys brachypetalus Benth. against Candida spp. and its toxicity in vivo assays - Camila de Paula Siqueira; Ralciane de Paula Menezes; Meliza Arantes Souza Bessa; Nágela Bernadelli Sousa Silva; Domingos Augusto João; Tiara da Costa Silva; Diego Godina Prado; Sérgio Antônio Lemos de Morais; Alberto de Oliveira; Francisco José Torres de Aquino; Luís Carlos Scalon Cunha; Carlos Henrique Gomes Martins (BMC Complementary Medicine and Therapies)
Abstract Background Given the few studies found in the literature and the search for new substances with antifungal and antivirulence activities against Candida spp., the use of natural products provides us with an effective treatment of infections with minimized side effects. This study was aimed at evaluating the toxicity and antifungal activity of Artabotrys brachypetalus Benth. extract and fractions against Candida spp. Methods This study evaluated the minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC), the ability to inhibit and/or eradicate preformed biofilm, and the ability to reduce and/or inhibit exoenzymatic production (hemolytic, phospholipase and proteinase) by Candida albicans, C. glabrata, C. krusei, C. parapsilosis and C. tropicalis against Artabotrys brachypetalus Benth. extract and fractions., The most active extract and fractions were analyzed by HPLC–ESI–MS for compound annotation. In vivo toxicity assays were performed on C. elegans larvae. Results HPLC–ESI–MS analysis showed mainly the presence of alkaloids in the ethanolic root extract and fractions of A. brachypetalus. The ethanolic root extract exhibited the most promising results, being fungicidal for C. glabrata with MIC/MFC of 375 µg/mL, MICB50/IC50 of 1.46 and 1.59 µg/mL. The biofilm eradication resulted in an IC50 of 0.00028 µg/mL against C. tropicalis. For the expression of introducer exoenzymes (½MIC), the ethanolic root extract showed a significant hemolytic activity of 42.7% against C. albicans; in assays on C. elegans, it demonstrated toxicity above a concentration of 1,000 µg/mL. In the tests, the fractions obtained from the root demonstrated more significant results than did the ethanolic extract. Conclusion The remarkable A. brachypetalus ethanolic root extract exhibits minimal toxicity in C. elegans assays, coupled with its potent antifungal, antibiofilm and antivirulence capabilities against Candida spp. marking it as a standout candidate for the control of these microorganisms.